Perbandingan Biaya Penggunaan Scaffolding Ringlock dan Scaffolding Frame Pada Pier Head (Studi Kasus: Proyek Pembangunan Jalan Akses Tol Makassar New Port Tahap 1 & 2): Bahasa Indonesia - Yanwar, Hauris; Mursalim; Kalangi, Hendry Tanoto (Jurnal Media Teknik Sipil, 2025)
The selection of the appropriate type of scaffolding plays a crucial role in determining project cost efficiency, work safety, and completion time. This study aims to analyze and compare the cost and installation duration between frame scaffolding and ringlock scaffolding used in the pier head construction of the Makassar New Port Access Road Project Phase 1 and 2, in order to provide recommendations for similar future projects. The research employed a descriptive comparative method with a case study approach, collecting field data to analyze differences in total cost and installation duration between the two scaffolding systems. The results show that ringlock scaffolding offers advantages in terms of installation ease and flexibility in adapting to various structural forms. Although its rental cost is higher than frame scaffolding, it provides greater efficiency by reducing installation time and labor costs. The monthly rental cost of ringlock scaffolding was Rp111,434,756.40 with an installation duration of 4.25 days, while frame scaffolding cost Rp63,508,060.00 with an installation duration of 9.40 days. The cost difference reached Rp47,926,696.40 (43%), and the installation duration difference was 5.15 days (54.79%). Therefore, ringlock scaffolding is considered more efficient for projects with tight schedules.